Pentingnya Manajemen Waktu Mahasiswa dalam Perspektif Konseling Lintas Budaya - Nurul Aisyah; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
College students have various academic and social responsibilities that require good time management skills to maintain a balance between their academic, organizational, and social lives. However, many students still struggle with time management, leading to academic procrastination, late assignment submissions, and low self-discipline. This study aims to determine the importance of student time management from a cross-cultural counseling perspective and to understand the factors influencing poor time management among students. The study employs a qualitative approach using a case study of a student identified as DV who struggles to balance time between classes, organizations, and social activities. Data collection techniques included observation, interviews, and documentation, while data analysis utilized the Miles and Huberman model. The results indicate that poor time management is influenced by procrastination habits, the influence of the social environment, and a collective culture that emphasizes togetherness. A behavioral counseling approach using self-management techniques helped the client improve self-discipline and the ability to set priorities. Thus, good time management is crucial in supporting students’ academic success and social balance.